Evaluating the Mechanisms of Improved Glucose Homeostasis after Bariatric Surgery in Ossabaw Miniature Swine. (24th August 2014) - Sham, Jonathan G.; Simianu, Vlad V.; Wright, Andrew S.; Stewart, Skye D.; Alloosh, Mouhamad; Sturek, Michael; Cummings, David E.; Flum, David R.
Abstract : Background . Roux-en-Y gastric bypass (RYGB) is the most common bariatric operation; however, the mechanism underlying the profound weight-independent effects on glucose homeostasis remains unclear. Large animal models of naturally occurring insulin resistance (IR), which have been lacking, would provide opportunities to elucidate such mechanisms. Ossabaw miniature swine naturally exhibit many features that may be useful in evaluating the anti diabetic effects of bariatric surgery. Methods . Glucose homeostasis was studied in 53 Ossabaw swine. Thirty-two received an obesogenic diet and were randomized to RYGB, gastrojejunostomy (GJ), gastrojejunostomy with duodenal exclusion (GJD), or Sham operations. Intravenous glucose tolerance tests and standardized meal tolerance tests were performed prior to, 1, 2, and 8 weeks after surgery and at a single time-point for regular diet control pigs. Results . High-calorie-fed Ossabaws weighed more and had greater IR than regular diet controls, though only 70% developed IR. All operations caused weight-loss-independent improvement in IR, though only in pigs with high baseline IR. Only RYGB induced weight loss and decreased IR in the majority of pigs, as well as increasing AUC insulin /AUC glucose . Conclusions . Similar to humans, Ossabaw swine exhibit both obesity-dependent and obesity-independent IR. RYGB promoted weight loss, IR improvement, and increased AUC insulin /AUC glucose, compared to the smaller changes following GJ and GJD, suggesting a combination of upper and lower gut mechanisms in improving glucose homeostasis.